Quality Assessment of Stevioside-Supplemented Biscuit by Analysing Its Effects on Liver Functions and Histomorphology of Rabbit - Kumar, Uttam; Hossain, Md Mahabub; Zaman, Md Mobin uz; Alam, Md Suzaul; Nahar, Most Aynun; Islam, Md Nazrul; Prodhan, Md Yeasin (Journal of the Bangladesh Agricultural University, 2025)
Stevioside (Stevia rebaudiana) is a small plant. Its leaves contain stevioside, a sweet compound that is 250–300 times sweeter than sucrose. Stevioside is a natural sweetener that is used as a sugar alternative and, hence, is a suitable choice for the diabetic patient. Some artificial sweeteners are used as sugar alternatives, which have more side effects than natural sweeteners. The present study was conducted to evaluate the effects of stevioside-supplemented biscuits on liver function in rabbits and to compare these effects with those of sugar- and saccharin-supplemented biscuits. For this purpose, three types of biscuits were prepared: stevioside-supplemented, sugar-supplemented, and saccharin-supplemented biscuits. Then, these biscuits were fed to rabbits to check their effects on the liver functions of rabbits. Therefore, four experimental groups, namely control (T1), stevioside (T2), sugar (T3), and saccharin (T4), were established, each containing three rabbits. Blood samples were collected on days 0, 7, 14, and 21 to determine the haematobiochemical profiles, including SGPT (serum glutamate pyruvate transaminase), SGOT (serum glutamate oxaloacetate transaminase), ALP (alkaline phosphatase), and RBS (random blood sugar). The results showed that the SGPT (22.35 U/L), SGOT (25.50 U/L), ALP (145.34 U/L), and RBS (4.8 mmol/L) levels in rabbits were lower in response to stevioside-supplemented biscuits. In contrast, the rabbits fed with sugar-supplemented biscuits had higher values (SGPT = 36.18 U/L, SGOT = 41.0 U/L, ALP = 292.22 U/L, and RBS = 6.31 mmol/L). Similarly, saccharin-supplemented biscuits also resulted in higher levels of SGPT = 50.08 U/L, SGOT = 56.0 U/L, ALP = 264.65 U/L, and RBS = 6.52 mmol/L) compared to stevioside-supplemented biscuits. Moreover, histological observations of the rabbits’ livers revealed that cytoplasmic glycogen storage in hepatic cells was higher in the stevioside-treated group than in the sugar- and saccharin-supplemented groups. Altogether, these results suggest that stevioside reduces SGPT, SGOT, ALP, and RBS levels than those of sugar and saccharin. It may serve as a suitable alternative to sugar. J Bangladesh Agril Univ 23(3): 410–418, 2025